2021
DOI: 10.1177/17151635211034528
|View full text |Cite
|
Sign up to set email alerts
|

Frequently asked questions about naloxone: Part 1

Abstract: Are patients and community members asking complicated questions about naloxone? The goal of this 3-part informational series is to increase pharmacists' knowledge on the frequently asked questions about naloxone, so that they can fill their own knowledge gaps as well as those of their patients. Pharmacists are key to ensuring all those at risk of an opioid overdose, or who are in a position to help, have naloxone and know how to use it. Beyond the signs and symptoms of opioid toxicity, naloxone administration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The answers to these FAQs were compiled through a series of literature reviews and can be found in the special series of the Canadian Pharmacists Journal. They are aimed at correcting misinformation and knowledge gaps related to naloxone [44][45][46]. This module will provide pharmacists with the tools needed to answer FAQs from patients and colleagues and correct any inaccurate perceptions pharmacists may have about naloxone.…”
Section: The Intervention Programmentioning
confidence: 99%
“…The answers to these FAQs were compiled through a series of literature reviews and can be found in the special series of the Canadian Pharmacists Journal. They are aimed at correcting misinformation and knowledge gaps related to naloxone [44][45][46]. This module will provide pharmacists with the tools needed to answer FAQs from patients and colleagues and correct any inaccurate perceptions pharmacists may have about naloxone.…”
Section: The Intervention Programmentioning
confidence: 99%